Nothing to gain by hating others - Azrymi, Amirul Nazmi (New Straits Times Press (M) Bhd., 2023)
This article reflects on the Quran-burning demonstration in Sweden circa Eiduladha 2023 and how it seems like a trend to become Islamophobes. It also talks on how it is easy to blame and hate Muslims today, and this can also happen in Muslim-majority nations like Malaysia. The article ends with a call to apply the Prophet's last sermon in our lives by loving and caring for each other without caveats.